The Architecture of Semantic Domains - Brandt, Per Aage (Theoria et Historia Scientiarum, 2008)
The expression ‘semantic domain’ is a spatial metaphor. In this article, it will be argued that it also expresses a necessary notion in semantic analysis. Anything meaningful is meaningful in a ‘context’; contexts supply relevant frames for the contents of our consciousness, and they thereby allow us to draw inferences from these contents. According to the view presented, contexts are structured within distinct semantic domains, which are grounded in bodily experience, not only in a basic sense, as referring to motor activities, but in the sense of a stable articulation of our life-world as an experiencable whole. The notion of semantic domain expresses this articulation in parts, regions, sorts of conceptual and practical behavior.